High burden of self-reported sexually transmitted infections among female sex workers in Togo in 2021 - Bitty-Anderson, Alexandra M.; Gbeasor-Komlanvi, Fifonsi A.; Bakoubayi, Akila W.; Tchankoni, Martin K.; Sadio, Arnold J.; Salou, Mounerou; Dagnra, Claver A.; Ekouevi, Didier K.; Coffie, Patrick A. (Frontiers in Public Health, 2022)
Background Sexually Transmitted Infections (STI) remain a public health challenge, especially for Female Sex Workers (FSW) who are particularly vulnerable. In sub-Saharan Africa where the overlapping epidemics of STI and HIV are concentrated among key populations, epidemiological data are needed in order to better understand STI trends in this population. The aim of this study was to assess the prevalence of self-reported STI symptoms and their risk factors among FSW in Togo in 2021. Methods A cross-sectional study was completed in June and July 2021 among FSW in two cities of Togo: in Lomé (capital city, south of Togo) and in Kara (north of Togo). A snowball sampling method was used and after consent, a standardized questionnaire was administered by trained research staff to collect information on STI. A multivariate logistic regression model was used to identify factors associated with self-reported STI. Results A total of 447 FSW, 300 in Lomé and 147 in Kara participated in this study. Median age was 30 [IQR: 24–38] and STI symptoms in the previous 12 months were reported by 191 FSW [42.7%, 95% CI: (38.1–47.5)], among whom 116 (60.7%) sought medical care. The most common reported symptoms were abnormal vaginal discharge (n = 78; 67.2%) and vaginal itching (n = 68; 58.6%). Current STI symptoms (at the time of the survey) were reported by 88 FSW (19.7%). In multivariable logistic regression, self-reported STI symptoms in the previous 12 months was negatively associated with living in the Lomé and older age and positively associated with having more than 15 clients in the previous week and being victim of violence. Conclusions Findings from this study reveal that the self-reported STI burden is relatively high among FSW Togo. Additional strategies are needed at the structural, medical, political and social levels to curb this trend and effectively aim at the elimination of STI epidemics by the year 2030.